DMSA-camSPECT/US fusion imaging of children’s kidneys – Proof of feasibility - Gühne, Falk; Weigel, Friederike; Kühnel, Christian; Seifert, Philipp; Freesmeyer, Martin (Nuklearmedizin - NuclearMedicine, 2020)
Aim SPECT using Tc-99m-dimercaptosuccinic acid (DMSA-camSPECT) and ultrasound (US) are useful diagnostic modalities in pediatric nephrology. Former studies proved SPECT/US fusion to be a problem-solving tool for thyroid and sentinel lymph node imaging. The purpose of this study was to demonstrate the feasibility of real-time DMSA-camSPECT/US fusion in children and to evaluate the technical implementation.Methods Subsequent to a clinical indicated DMSA-camSPECT showing a mostly normal result, 10 children received a SPECT/US fusion. The magnetic sensor-navigated equipment allows a real-time superposition of three-dimensional SPECT data to live US images according to the position of the transducer.Results 100 % of still images and 90 % of cine-loops were sufficient to depict the kidney; at least one sufficient camSPECT/US fusion loop could be accomplished for every kidney examined. Limitations are mainly caused by standard difficulties of conventional US.Conclusion Real-time DMSA-camSPECT/US is feasible in depiction of renal parenchyma. This newly implemented application broadens the scope of SPECT/US fusion imaging.
Keywords: DMSA; SPECT; ultrasound; kidney; children